1998
DOI: 10.2486/indhealth.36.209
|View full text |Cite
|
Sign up to set email alerts
|

Long Commuting Time, Extensive Overtime, and Sympathodominant State Assessed in Terms of Short-Term Heart Rate Variability among Male White-Collar Workers in the Tokyo Megalopolis.

Abstract: To investigate the possible effects of long commuting time and extensive overtime on daytime cardiac autonomic activity, the short-term heart rate variability (HRV) both at supine rest and at standing rest of 223 male white-collar workers in the Tokyo Megalopolis was examined. Workers with a one-way commute of 90 min or more exhibited decreased vagal activity at supine rest and increased sympathetic activity regardless of posture, and those doing overtime of 60 h/ month or more exhibited decreased vagal activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 35 publications
(1 reference statement)
2
50
0
1
Order By: Relevance
“…Five studies (30,31,44,45,48) did not control for covariates and reported only univariate between-subject associations. Four studies (26,28,33,38) reported van der Hulst that included a particular outcome measure found an association with long workhours, the direction of the association (+ or -) is given in the last column of the table. If the association was found in more than one study and all studies that found an association corrected for covariates, a double plus (++) or a double minus (--) is used to indicate that the evidence for this association was particularly strong.…”
Section: Methodological Characteristics and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies (30,31,44,45,48) did not control for covariates and reported only univariate between-subject associations. Four studies (26,28,33,38) reported van der Hulst that included a particular outcome measure found an association with long workhours, the direction of the association (+ or -) is given in the last column of the table. If the association was found in more than one study and all studies that found an association corrected for covariates, a double plus (++) or a double minus (--) is used to indicate that the evidence for this association was particularly strong.…”
Section: Methodological Characteristics and Resultsmentioning
confidence: 99%
“…Mean 24-hour heart rate was significantly higher in a long workhour period (74 beats/minute) than in a relatively short workhour period (69 beats/minute) in a within-subject study (30). Respiratory sinus arrhythmia (heart rate variability with a frequency between 0.15 and 0.30 Hz, used as an indicator of activity of the vagus nerve or the parasympathetic nervous system) was included in four studies (31,33,44,45). Only one (33) found lower respiratory sinus arrhythmia during standing rest for those who worked extended hours (but not while lying down and only for one of the two indicators of the disorder); the other studies found no relationship.…”
Section: Physiological Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Kageyama et al, (1998) studied the short-term heart rate variability of 223 male white-collar workers in Tokyo and found those commuting more than 90 minutes one-way had chronic stress and fatigue symptoms which can induce cardiovascular abnormalities and dysfunctions related to the inset of heart disease. Walsleben et al (1999) found rail commuters in Long…”
mentioning
confidence: 99%
“…Two possible explanations for this are (1) that people working long hours on weekdays spend holidays attending to personal matters that cannot be taken care of on weekdays and (2) that they became accustomed to a short sleep duration. Kageyama and colleagues reported that the amount of overtime was positively correlated with the amount of time spent sleeping on the nights before holidays 4) ; however, a later report stated that sleep length before holidays was inversely correlated with overtime 7) . This latter result concurs with that of our study.…”
Section: Discussionmentioning
confidence: 99%